A new standard genetic map for the laboratory mouse. - Cox, A; Ackert-Bicknell, C; Dumont, B; Ding, Y; Bell, J; Brockmann, G; Wergedal, J; Bult, C; Paigen, B; Flint, J; Tsaih, S; Churchill, G; et al. (2009)
Genetic maps provide a means to estimate the probability of the co-inheritance of linked loci as they are transmitted across generations in both experimental and natural populations. However, in the age of whole-genome sequences, physical distances measured in base pairs of DNA provide the standard coordinates for navigating the myriad features of genomes. Although genetic and physical maps are colinear, there are well-characterized and sometimes dramatic heterogeneities in the average frequency of meiotic recombination events that occur along the physical extent of chromosomes. There also are documented differences in the recombination landscape between the two sexes. We have revisited high-resolution genetic map data from a large heterogeneous mouse population and have constructed a revised genetic map of the mouse genome, incorporating 10,195 single nucleotide polymorphisms using a set of 47 families comprising 3546 meioses. The revised map provides a different picture of recombination in the mouse from that reported previously. We have further integrated the genetic and physical maps of the genome and incorporated SSLP markers from other genetic maps into this new framework. We demonstrate that utilization of the revised genetic map improves QTL mapping, partially due to the resolution of previously undetected errors in marker ordering along the chromosome.